Keterkaitan Efikasi Diri dan Penyesuaian Diri: Kunci Sukses Menghadapi Tantangan Baru - Agmeilia, Irene Friska; Suroso, Suroso; Rista, Karolin (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
Self-adjustment is a process of behavior and ability possessed by individuals to interact or deal with situations and demands from their surrounding environment, enabling individuals to accept and display positive attitudes towards themselves and others. This research aims to analyze the relationship between self-efficacy and self-adjustment in learning among new students of the Faculty of Psychology at Universitas 17 Agustus 1945 Surabaya. The research was conducted using a quantitative correlational research method, employing accidental sampling techniques with a sample size of 210 students. The measurement instruments used were the self-efficacy scale and the self-adjustment scale. The data were analyzed using the Pearson product-moment correlation technique with the assistance of IBM SPSS Statistics software version 25 for Windows. The analysis results revealed a highly significant positive relationship between self-efficacy and self-adjustment among new students of the Faculty of Psychology. Penyesuaian diri merupakan suatu proses tingkah laku dan kemampuan yang dimiliki oleh individu untuk mampu berinteraksi atau menghadapi situasi dan tuntutan dari lingkungan sekitarnya, sehingga individu mampu menerima dan menunjukkan sikap baik kepada diri sendiri dan orang lain. Penelitian ini bertujuan untuk menganalisis hubungan antara efikasi diri dengan penyesuaian diri dalam belajar pada mahasiswa baru fakultas psikologi Universitas 17 Agustus 1945 Surabaya. Penelitian ini dilakukan dengan metode penelitian kuantitatif korelasional, menggunakan teknik accidental sampling dengan sampel 210 mahasiswa. Alat ukurnya menggunakan dua skala yaitu skala efikasi diri dan skala penyesuaian diri menggunakan teknik korelasi pearson product moment dengan bantuan program SPSS Seri 25 IBM For Windows. Hasil analisis menunjukkan bahwa terdapat hubungan positif yang sangat signifikan antara efikasi diri dengan penyesuaian diri pada mahasiswa baru fakultas psikologi.